Inverse problems for the heat-conduction equation with nonlocal boundary conditions - Ivanchov, N. I. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Conditions under which the time-dependent temperature conductivity coefficient is determined uniquely are established in the case where the boundary conditions and the overdetermination conditions are non local.